Female Facial Attractiveness Assessed from Three-Dimensional Contour Lines by University Students - Jinwara Jirathamopas; Yu Fang Liao; Ellen Wen-Ching Ko; Yu-Ray Chen; Chiung Shing Huang (MDPI AG, 2018)
Background: Three-dimensional (3D) images could provide more accurate evaluation for facial attractiveness than two-dimensional (2D) images. The 3D facial image could be simplified into gray scale 3D contour lines. Whether female facial attractiveness could be perceived in these simplified 3D facial contour lines should be determined. Methods: A series of 100 2D photographs (one frontal and two lateral views) and 3D contour lines extracted from 3D facial images of females were projected onto a screen. Each image presentation lasted 5 s, and the evaluators marked their impression of each image’s facial attractiveness on a five-point Likert scale within 3 s of its presentation. The evaluation of the 3D contour lines was performed twice, 2 weeks apart. The evaluators were university students. Results: High consistency (r = 0.92) was found for the first and second evaluation of 3D facial contour lines for female facial attractiveness. The judgments of unattractive face were more consistent than the judgments of attractive face. Male students tended to give lower scores than female students in the evaluation of female facial attractiveness. Conclusions: Female facial attractiveness could be evaluated by 3D facial contour lines. 3D facial contour lines should be one of the key factors of facial attractiveness.